2021
DOI: 10.1021/acs.est.0c06620
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic and Teratogenic Effects of Iodoacetic Acid Drinking Water Disinfection Byproduct in Vitro and in Vivo

Abstract: Iodoacetic acid (IAA) is the most genotoxic iodinated disinfection byproduct known in drinking water. Previous studies have shown that IAA may be an endocrine disruptor. However, whether IAA has reproductive and developmental toxicity remains unclear. In this study, the reproductive and developmental toxicity of IAA was evaluated using a battery of in vitro and in vivo reproductive/developmental toxicity screening tests. The results of E-Screen, uterotrophic, and H295R steroidogenesis assays were negative. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Thus, IAA also inhibits several enzymes in many cells and biological pathways, since it is an inhibitor of cysteine-dependent enzymes at the active site [ 38 ]. In addition to glycolysis and specific GAPDH inhibition, it also induces in vivo toxicity [ 39 ]. In future, it might require further proof on gintonin effects against ROS using another model system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IAA also inhibits several enzymes in many cells and biological pathways, since it is an inhibitor of cysteine-dependent enzymes at the active site [ 38 ]. In addition to glycolysis and specific GAPDH inhibition, it also induces in vivo toxicity [ 39 ]. In future, it might require further proof on gintonin effects against ROS using another model system.…”
Section: Discussionmentioning
confidence: 99%
“…Iodoacetic acid (IAA) was observed to show AR binding in vitro [50]. Despite the discrepancies between this result and others, studies have still demonstrated that IAA is a potential disruptor of human AR (hAR) [51]. The differences in research results may be due to factors such as the selection of species of cells and diverse endpoints.…”
Section: Hormone Receptor-mediated Mechanism Of Endocrine Disruptionmentioning
confidence: 89%
“…The available literature was further refined by considering whether MIEs were defined or not. Finally, 32 studies related to the endocrine system-disrupting effects of DBPs were selected in the present investigation [ 28 , 49 , 50 , 51 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. As expected, most of the research on the endocrine-related detrimental effects of various DBPs were published in the last ten years even though the first publication dated back to 2003 (only seven publications from 2000 to 2009 and 25 from 2010 until now) ( Figure 1 ).…”
Section: Performance Of Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haloacetic acids are the second most prominent class of disinfection by-products, and are frequently detected in surface and drinking water systems. These compounds have genotoxic, mutagenic, cytotoxic, and tumorigenic effects in humans (Kim et al, 2020;Long et al, 2021;. In metabolically engineered Burkholderia species, the degradation activity of haloacetic acids can be increased by 4-8 times (Su et al, 2013).…”
Section: Environmental Bioremediationmentioning
confidence: 99%